Correlation between low-proficiency in english and negative perceptions of what it means to be an english speaker - Kavarljit Kaur Gill; Andrew N. Williams (2013)
Learning another language is very much affected by positive or negative connotations attached to the new language by the language learner. Entering Malaysia public universities there are many students with a low profeciency in english, despite spending eleven years studying english in school. Could it be that the lack of progress among these students could be attributed to a negative view of what it means to be a speaker of english? This study investigated the perceptions of students at a public university, to determine whether there is a correlation between low-proficiency and negative perceptions of what it means to be an english speaker. Analysis of the results showed that Malaysian students have a very positive perception of what it means to be an english speaker.